The relationship between institutions and trade, empirical analysis from the Republic of Moldova case - Ion MUȘCHEI (Eastern European Journal of Regional Studies)
Starting from the fact that the Republic of Moldova has signed the Association Agreement with the European Union and moreover creates a Deep and Comprehensive Free Trade Area, the current paper aims to analyse the relationship between institutions and trade. The existing theory of institutionalism pointed out that country with the same level of institutions tend to trade more and also trade might produce institutional change. Based on a mix of methods analyses like reports, data and survey, this paper concludes that the correlation between institution and trade in this case is law. This is relevant because in this way we can change, enrich or enhance the strategy of the EU towards Eastern countries especially the Republic of Moldova.